Effects of lipid phase transition of the freeze-cleaved envelope of Escherichia coli. - Bayer, M E (1977)
We studied the fine structure of the envelope of Escherichia coli auxotroph K1060 after the cells were grown in the presence of one of the following fatty acids; oleic, palmitelaidic, or elidic acid. The cells were freeze-fractured after exposure to temperatures above and below the lipid phase transition range. As judged by freeze-etching methods, we observed that below the transition range the fracture plane of the inner membrane showed the typical aggregation of intramembranous particles (IMP) and concomitant development of areas devoid of IMP. In these areas we found a regular arrangement of equally spaced ridges, often intersected at 90 degrees by arrays of similar ridges. The ridges were composed of spherical particles measuring 4 to 5 nm in diameter. Formation and melting of these arrays took place within 15 to 30s after temperature shift-down or shift-up, respectively. Fixation in glutaraldehyde prevented these changes. The outer-membrane fracture plane revealed ordered areas to a lesser degree; these were discernible only by the regular arrangement of the IMP of the concave fracture plane. We interpret the data by suggesting that the pattern of ridges in E. coli K1060 is analogous to the band patterns described for artificial liposomes, and that the particles, possibly proteins, are lined up or extruded along the ridges during membrane lipid crystallization.